Distribution of causes of death and associated organ injuries in road traffic accident-related fatalities: a postmortem study in Addis Ababa, Ethiopia - Gashaw Sete; Selam Temesgen Alemu (BMC Public Health)
Abstract Background According to the World Health Organization (WHO), there were 1.19 million road traffic accident (RTA)-related deaths in 2021, with a significantly higher death rate in developing countries than in developed countries. Objective To assess the distribution of causes of death and associated organ injuries in RTA-related fatalities. Methods This retrospective cross-sectional study was conducted at the Department of Forensic Medicine and Toxicology of Saint Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia. This study included 207 autopsies of RTA-related deaths. Results Among the 198 victims, 70.7 percent were males and 29.3 percent were females, with a mean age of 36.65 (years). The leading causes of death were craniocerebral injury (36.9%) and polytrauma (14.6%). The majority (49%) died in the prehospital setting, 37.9% at the hospital, and 5.6% at home. Pedestrians were the most affected (71%), followed by passengers (16%). Urban areas had a higher incidence of accidents (58.1%). All victims had soft tissue injuries, with 75.3% sustaining head injuries, 58.6% sustaining musculoskeletal injuries, and 51% sustaining thoracic injuries. Conclusion Addressing RTA-related deaths requires a multifaceted approach involving various stakeholders. Building a prehospital emergency service, providing first aid training, and continuous professional development training to health professionals are also important.